IMPLEMENTASI TEORI BELAJAR MELALUI DESAIN MEDIA EDUKATIF MENGGUNAKAN CANVA PADA SISWA SMKN 1 TAKALAR - Nur Insan; Mantan Mutia S; Maman A. Majid Binfas; Nur Arafah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Research The development of digital technology in the world of education requires innovation in the learning process that is not only visually appealing, but also has a strong theoretical foundation. This study aims to analyze the implementation of learning theory in educational media design using Canva and its relevance in increasing student engagement. This study uses a qualitative approach that is descriptive with data collection techniques through observation, interviews, and documentation. The results of the study show that Canva-based learning media designed based on the theories of behaviorism, cognitivism, and constructivism can increase students' attention, understanding, and activeness. In addition, this media also provides a more meaningful learning experience because it integrates the visual aspects and cognitive processes of students. Thus, the implementation of behaviorism, cognitivism, and constructivism theories in educational media design using Canva has been proven to support the creation of a more effective, interactive, and meaningful learning process and in accordance with the sub-topics of learning and learning courses. Therefore, Canva can be used as an innovative learning media alternative to improve the quality of learning in schools, especially at SMK Negeri 1 Takalar.